Trading Auntie: the exploitation and protection of intellectual property rights during the BBC’s monopoly years - Johnson, Catherine (Routledge, 2009)
Most histories of British television date the emergence of a trade in programming to the mid- to late-1950s when recording technologies turned previously ephemeral programmes into exchangeable goods and ITV brought a commercial impetus to British broadcasting. However, this historicisation of British broadcasting fails to acknowledge that the BBC was engaged in selling the rights to its programming before the arrival of commercial television in 1955. By exploring the sale of rights to two key programmes in the period between 1946 and 1955 (the radio serial Dick Barton and the television serial The Quatermass Experiment) this article demonstrates the ways in which the BBC operated within a broader set of commercial industries and engaged in commercial practices even while it had a public service monopoly on broadcasting. However, this article argues that the BBC’s trade in rights was not primarily motivated by financial gain, but rather by the corporation’s need to protect the integrity of its programming and its corporate identity. While contemporary accounts of the trade in intellectual property equate it with an increased commercialisation in British broadcasting, this history points to the importance of propriety in understanding the function of the trade in intellectual property historically and today.